Designing a digital marketing strategy model at sanggar bunga nirwana using a grounded theory approach - Siti Aisyah Jamal; Alizar Hasan; Innsanul Kamil (Enrichment : Journal of Management, 2022)
One of the ornamental plant shops in Agam Regency, which is in Payakumbuh, West Sumatra, is Nirwana Flower Studio Business. Nirwana Ornamental Flower Studio is a small and medium-sized industrial enterprise because it makes a small amount of money and has a small number of employees. The Nirwana Ornamental Flower Studio had trouble running its business because it didn't have enough customers and couldn't compete with similar businesses. One reason why this studio doesn't make enough money is that their advertising and sales are still boring and boring. The Grounded Theory method is what is used. Grounded Theory is a qualitative method that can be used to make sure that Sanggar Bunga Nirwana has the right marketing strategy model for their business right now. There are 15 important indicators that need to be taken into account when making a model for a digital marketing strategy. The six most important ones are the readiness of human resources, the availability of technology, the capabilities of the company, the support infrastructure, the uniqueness of the product, and customer expectations.